High-resolution record of Paleoclimate during the late Quarternary, recovered from Con Moong cave - North Vietnam - Luu Thi Phuong, Lan; B. Ellwood, Brooks; Nguyen Khac, Su; Hsung Wang, Wei-; Doan Dinh, Lam; Nguyen Thanh, Dung; Nguyen Thi, Mai (Vietnam Journal of Earth Sciences, 2023)
To clarify the paleoclimatic events in Northern Vietnam during the Late Quaternary, 132 Con Moong - Thanh Hoa cave sediment samples were collected to analyze magnetic susceptibility (χ), δ18O, and δ13C. Based on the tendency in the value of χ  Con Moong's sediment, 14 climate zones that change continuously from warm to cold were identified. These climate zones also correspond to the changing trend of δ18O and δ13C. The period of 14 magnetic zones is referenced from the extrapolation of four 14C data. These alternating cold-warm χ sequences correspond to the Composite Reference Section (CRS) developed in Southern Europe from a χ zonation of multiple caves. The paleoclimate characteristics, including the Heinrich H2 and H1 climate events, the Bølling/Allerød, and Younger Dryas warm-cold events, were elucidated for Northern Viet Nam from ~28.000 to ~10.000 yr BP.